2002
DOI: 10.1090/s0002-9939-02-06795-3
|View full text |Cite
|
Sign up to set email alerts
|

Periodic solutions for planar 2N-body problems

Abstract: Abstract. In this paper we study some necessary conditions and sufficient conditions for the nested polygonal solutions of planar 2N-body problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 8 publications
0
16
0
2
Order By: Relevance
“…For p = 2 and n = 2, 3, 4, 5, 6 in [28], and for p = 2 and n ≥ 2 Zhang and Zhou [49] proved that there are central configurations of the 2n-body problem where n bodies with equal mass are in the vertices of a regular n-gon, and the remainder n bodies with equal mass but not necessarily equal to the previous n bodies, are also in the vertices of another regular n-gon homothetic to the first n-gon.…”
Section: Planar Nested Central Configurationsmentioning
confidence: 99%
“…For p = 2 and n = 2, 3, 4, 5, 6 in [28], and for p = 2 and n ≥ 2 Zhang and Zhou [49] proved that there are central configurations of the 2n-body problem where n bodies with equal mass are in the vertices of a regular n-gon, and the remainder n bodies with equal mass but not necessarily equal to the previous n bodies, are also in the vertices of another regular n-gon homothetic to the first n-gon.…”
Section: Planar Nested Central Configurationsmentioning
confidence: 99%
“…In 1985, Perko and Walter [4] showed that for ≥ 4, masses at the vertices of a regular polygon rotating about their common center of masses with an appropriate angular velocity describe a periodic solution of the -body problems if and only if the masses are equal. In 1995 and in 2002, Moeckel and Simo [5] and Zhang and Zhou [6] studied the sufficient and necessary conditions for planar nested 2 -body problems. In this paper, we study the following problems.…”
Section: ) Is a Central Configuration If And Only Ifmentioning
confidence: 99%
“…Um resultado similar ao Teorema 2.1 pode ser encontrado no Corolário 5, p. 2164 da Ref. [12]. Gostaríamos de salientar que na Ref.…”
Section: Observações Finaisunclassified